Credit supply and the housing boom - Alejandro Justiniano; Giorgio E. Primiceri; Andrea Tambalotti (Federal Reserve Bank of New York, 2015)
The housing boom that preceded the Great Recession was the result of an increase in credit supply driven by looser lending constraints in the mortgage market. This view on the fundamental drivers of the boom is consistent with four empirical observations: the unprecedented rise in home prices, the surge in household debt, the stability of debt relative to home values, and the fall in mortgage rates. These facts are difficult to reconcile with the popular view that attributes the housing boom to looser borrowing constraints associated with lower collateral requirements. In fact, a slackening of collateral constraints at the peak of the lending cycle triggers a fall in home prices in our framework, providing a novel perspective on the possible origins of the bust.
Keywords: E32; E44; 330; housing and credit boom; house prices; collateral constraints; leverage restrictions